Validation of an HPLC method for quantification of anti-inflammatory markers in an ethanolic extract of Sahastara and its anti-inflammatory activity in vitro - Narin Kakatum; Arunporn Itharat; Weerachai Pipatrattanaseree; Puritat Kanokkangsadal; Neal M Davies (Wolters Kluwer Medknow Publications, 2021)
Background and purpose: Sahastara (SHT) is a traditional Thai medicine for the treatment of musculoskeletal and joint pain. It consists of 21 plant components. A previous study demonstrated the anti-inflammatory activity of SHT on inhibition of nitric oxide production and prostaglandin E2 (PGE2) production, however, inhibitory effects on tumor necrosis factor-alpha (TNF-α) has not been reported. In this study, we evaluated the anti-inflammatory activity of SHT on inhibitory effects on TNF-α and PGE2 production and presented an analytical method for validation of SHT. Experimental approach: Anti-inflammatory activity was evaluated by inhibitory activity on TNF-α and PGE2 production in RAW264.7 cells. The validated procedure was conducted according to ICH guidelines. The validated parameters were specificity/selectivity, linearity, range, the limit of detection (LOD), and limit of quantitation (LOQ). Findings/Results: Ethanolic extract of SHT exerted inhibitory activity on PGE2 production in RAW264.7 cells with IC50 16.97 ± 1.16 μg/mL. Myristica frangrans seed extract showed the highest inhibitory activity on PGE2 production. Piper retrofractum extract showed the highest inhibitory activity on TNF-α production. For the HPLC method, all validated parameters complied with standard requirements. Each analyzed peak showed good selectivity with a baseline resolution greater than 1.51. The linearity of all compounds was > 0.999. The % recovery of all compounds was within 98.0-102.0%. The precision of all compounds was less than 2.0% CV. Conclusion and implications: Ethanolic extracts of SHT possess anti-inflammatory activity by inhibition of TNF-α and PGE2 production in vitro. This study provides support for the traditional use of SHT. The validated results showed good specificity/selectivity, linearity, precision, and accuracy with appropriate LOD and LOQ. This study is the first report on the validation of the HPLC method of SHT for use as quality control of the SHT extract.